PEMILIHAN TOPIK PENELITIAN DI PROGRAM STUDI ADMINISTRASI RUMAH SAKIT - William Indara S Mooduto; Nur Irna M. J. Ahiri; Sri Sucy Van Gobel (Journal of Hulonthalo Service Society (JHSS), 2022)
Research in the Hospital Administration Study Program plays an important role in improving the quality of health services in Indonesia. However, selecting the right research topic is often a challenge for students and study program managers. The purpose of this community service is to provide guidance in selecting relevant, quality research topics that have a direct impact on the hospital sector. The method used is a workshop approach and focus group discussion (FGD) involving students, lecturers, and the hospital. The results of this community service indicate that selecting research topics that focus on service quality management, health information technology, and hospital policies can increase the contribution of study programs in the health sector. Through this community service, participants are able to identify the research areas that are most relevant to the needs of the hospital industry.